Prioritizing coastal wetlands for marsh bird conservation in the U.S. Great Lakes. (September 2020) - Grand, Joanna; Saunders, Sarah P.; Michel, Nicole L.; Elliott, Lisa; Beilke, Stephanie; Bracey, Annie; Gehring, Thomas M.; Gnass Giese, Erin E.; Howe, Robert W.; Kasberg, Bradford; Miller, Nathaniel; Niemi, Gerald J.; et al.
Abstract: Human activity surrounding the Laurentian Great Lakes basin has significantly degraded coastal wetland habitats, resulting in severe marsh bird population declines and reduced coastal resilience to changing environmental conditions. Given the need to conserve remaining coastal wetlands for wildlife and people, we developed a spatial prioritization to identify the most important U.S. Great Lakes coastal wetlands for 14 marsh bird species. We modeled occurrence and relative abundance of each species using boosted regression trees, a machine learning algorithm, to relate standardized monitoring data to ten remotely-sensed environmental covariates. We then used Zonation conservation planning software to rank every wetland cell based on its importance for the suite of marsh bird species. Evaluation of the drivers of marsh bird occurrence and abundance revealed that open water, herbaceous wetland, latitude, longitude, and impervious surface were the most important predictors across focal species. The high-priority wetlands for marsh birds (defined as grid cells ranked in the top 20%) occurred along the shores of eastern Lake Ontario, western Lake Erie/St. Clair, Saginaw Bay, Green Bay, northern lakes Michigan and Huron, and western Lake Superior. Overall, less than half (42%) of high-priority coastal wetlands across the Great Lakes basin are currently under some level of protection, with Lake Ontario priority wetlands being the least protected (25%). Our findings represent an opportunity to improve coastal wetland conservation in a region where wetland loss and degradation continue to threaten marsh bird populations and the integrity of one of the world's largest freshwater ecosystems.